STRATEGY OF PUBLIC SERVICE TO IMPROVE SERVICE QUALITY AT THE INSTITUTE OF LEARNING DEVELOPMENT AND PROFESSION (LP3) STATE UNIVERSITY OF SURABAYA - Wismanadi, Himawan; Nuryono, Wiryo; Suhartiningsih, Suhartiningsih; Meirinawati, Meirinawati (Natapraja, 2021)
The implementation of a clean and effective government is a constitutional obligation and the hope of all citizens. In reality, these rights have not been fully obtained by the community. This is reflected in the number of complaints or public reports to the Ombudsman Institution to help handle complaints related to the performance of public services by government agencies. Based on the incoming reports, it can be seen that State Higher Education Institutions are ranked 12th based on the number of reports. One of these State Universities is the State University of Surabaya (Unesa). Unesa has an institution, one of which is called the Learning and Professional Development Institute (LP3) which has 7 (seven) centers, namely the Teacher Professional Education Center, Training Development Center, Professional Certification Center, Learning Strengthening Center, Core and Institutional MPK Management Center, Character Development Center and Counseling Services and Psychological Service Centers. The purpose of this study was to obtain an overview of the Public Service Strategy to Improve Service Quality at the Institute for Learning and Professional Development (LP3), State University of Surabaya. This type of research was developed using qualitative research. Sources of data from informants, events and documents. Data collection techniques through interviews, observation, documentation and triangulation. Data analysis is done by collecting data, reducing data, displaying data and drawing conclusions. Empirical data is needed to improve public services through LP3 Unesa. The information obtained can be used as a basis for establishing strategic policies that will help improve the quality of public services. The theory used in the opinion of Osborne (2001) there are 5 (five) strategies to improve the performance of public services. The strategies are Core Strategy, Consequences Strategy, Customer Strategy, Control Strategy, Culture Strategy.